The functional TNF-α−308G > a single-nucleotide polymorphism (rs1800629): association with the predictive indices of breast cancer carcinogenesis - Refaat, Sherif; Al-Rashidi, Hanan E.; El Azeem, Rania A. Abd; Nouh, Walaa E.; Hamed, Sahar; Attia, Zeinab R. (Breast cancer research and treatment, 2025)
Background Compared with all other cancer types, Breast cancer (BC) among women has now exceeded them all as the primary reason for cancer worldwide. The BC represents 11.7% of all cancer cases and accounts for a predestined 2.3 million new cases. It is the fourth primary reason for cancer-associated deaths in women. With a staggering 200–400% increase in the relative incidence of BC in Egypt, there is an urgent need for new diagnostic or predictive markers. Purpose The current investigation aims to explore the connection of the functional TNF-α −308 G > A (rs1800629) single-nucleotide polymorphism (SNP) with different breast cancer predictive indices. Methods The ARMS-PCR method was used for genotyping TNF-α −308 G > A SNP. Three groups were recruited for the study: 79 patients with benign breast inflammation (BBI); 163 with breast cancer (BC) and 144 controls (C). Results The TNF-α −308 G > A SNP was distributed among different groups in a unique pattern; in the control group 63.9% of cases were in the GG, 34% were in the GA, and 2.1% were in the AA. The BC group had 14% GG, 79% GA, and 7% AA, while the BBI group had 24% GG, 76% GA, and 0% AA. The AA genotype and A allele represented a strong significant correlation with risk factors in the BC group (OR AA : 14.67 [95% CI = 3.78–56.91] and OR A : 0.27 [95% CI = 0.19–0.39], respectively; P < 0.0001) in contrast to the control group. However, in the BBI group, a strong significant correlation was noted with the GA genotype (OR GA : 5.93 [95% CI = 3.18–11.04] P < 0.0001). In the BC group, the AA genotype shows a significant increase in Nottingham Prognostic Index (NPI) in positive ER and PR in contrast to the relevant negative ones ( P = 0.02 and 0.002, respectively). However, the GA genotype significantly increased NPI in positive Her2 and metastatic patients ( P = 0.03 and 0.01, respectively). Conclusion This research is the first to correlate TNF-α −308 G > A (rs1800629) SNP in Egyptian BC patients. The A allele, GA & AA genotypes, and the Overdominant model of the TNF-α −308 G > A gene variants were recorded as prognostic risk factors for BC carcinogenesis.